The volume of the solid formed by revolving the curve
y = x 1 − x + 1 1
bounded between x = 8 1 and x = 1 6 9 around the x -axis is in the the form A π ln C B .
If A and B are square-free, what is the value of A × B × C ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
can you please explain how volume of revolution = integral (pi) y^2
Log in to reply
Vighnesh, sorry, I didn't explain it clearly. Imagine you cut a small slice δ x under the curve y and you revolve it along the x -axis. You will get a thin disk of radius y and thickness δ x therefore its volume is cross-sectional area × thickness ⇒ δ V = π y 2 δ x .
To find the volume of revolution of y along the x -axis from x = a to x = b we do: n → ∞ lim π 0 ∑ n y 2 δ x = π ∫ a b y 2 d x .
You should find this in calculus textbooks or on Volume of Revolution - Disc Method
Log in to reply
Oh!!! Thnx a lot Chew-Seong for your kind help....
@Steven Zheng This is not a solution, but I just thought I should point out a potential ambiguity. Note that π ∗ ln ( 1 6 2 5 ) = 2 π ∗ ln ( 4 5 ) , thus 1 ∗ 2 5 ∗ 1 6 = 4 0 0 and 2 ∗ 4 ∗ 5 = 4 0 would both be valid answers. To avoid this ambiguity, you might want to specify that A , B , C are integers with A , B being square-free.
Edit: Now for an actual solution .....
Using the disk method, we have that the volume of revolution is
∫ a b π y 2 d x = π ∫ a b ( x 1 + x + 1 1 − x ( x + 1 ) 2 ) d x = π ∗ ln ( x ( x + 1 ) ) − π ∗ R
evaluated from a = 8 1 to b = 1 6 9 , where
R = 2 ∫ a b x 2 + x + 4 1 − 4 1 d x = 2 ∫ u 2 − 1 d u ,
where I have made the substitution u = 2 x + 1 .
Now let u = sec ( θ ) , making d u = sec ( θ ) tan ( θ ) d θ and u 2 − 1 = tan ( θ ) . We then end up with
R = 2 ∫ sec ( θ ) d θ = 2 ∗ ln ( sec ( θ ) + tan ( θ ) ) = 2 ∗ ln ( 2 x + 1 + 2 x ( x + 1 ) )
evaluated from a to b . Plugging in the values for a and b yields a volume of
π ( ln ( 2 5 6 2 2 5 ) − 2 ln ( 4 ) − ( ln ( 6 4 9 ) − 2 ln ( 2 ) ) ) = 2 π ln ( 4 5 ) .
Thus A ∗ B ∗ C = 2 ∗ 5 ∗ 4 = 4 0 .
Nice solution; I used the same method. Thank you Steven Zheng for the excellent problem too.
Problem Loading...
Note Loading...
Set Loading...
The required integral is:
I = π ∫ 8 1 1 6 9 y 2 d x = π ∫ 8 1 1 6 9 ( x 1 − x + 1 1 ) 2 d x
= π ∫ 8 1 1 6 9 ( x 1 − x ( x + 1 ) 2 + x + 1 1 ) d x
= π ( ∫ 8 1 1 6 9 x d x − 2 ∫ 8 1 1 6 9 x ( x + 1 ) d x + ∫ 8 1 1 6 9 x + 1 d x )
= π ( I 1 − 2 I 2 + I 3 )
I 1 = ∫ 8 1 1 6 9 x d x = [ ln x ] 8 1 1 6 9 = ln ( 1 6 9 ) − ln ( 8 1 ) = ln ( 1 6 9 × 1 8 ) = ln ( 2 9 )
Similarly, I 3 = ln ( 1 8 2 5 )
I 2 = ∫ 8 1 1 6 9 x ( x + 1 ) d x = ∫ 8 1 1 6 9 ( x + 2 1 ) 2 − 4 1 d x = ∫ 8 1 1 6 9 ( 2 x + 1 ) 2 − 1 2 d x
Now substituting 2 x + 1 = sec θ , then:
I 2 = ∫ sec − 1 4 5 sec − 1 8 1 7 sec 2 θ − 1 2 ( 2 1 ) sec θ tan θ d θ = ∫ sec − 1 4 5 sec − 1 8 1 7 sec θ d θ
= ln ∣ sec θ + tan θ ∣ sec − 1 4 5 sec − 1 8 1 7 = ln ( 8 1 7 + 8 1 5 ) − ln ( 4 5 + 4 3 )
= ln 4 − ln 2 = ln 2
⇒ I = π ( I 1 − 2 I 2 + I 3 ) = π ( ln ( 2 9 ) − 2 ln 2 + ln ( 1 8 2 5 ) )
= π ln ( 2 9 × 2 2 1 × 1 8 2 5 ) = π ln ( 1 6 2 5 ) = 2 π ln ( 4 5 )
⇒ A = 2 , B = 5 and C = 4 ⇒ A × B × C = 4 0